2007
DOI: 10.1002/mawe.200700240
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental approaches of bacteria‐biomaterial interactions

Abstract: Bacterial adhesion to surfaces is a complicated process influenced by many factors including the bacteria (surface energy and charge, molecular details), the substratum surface (chemical composition, roughness, configuration, surface energy and charge) and environmental factors (serum proteins, flow conditions, temperature, bacterial concentration, time of exposure, antibiotics). The models that have been proposed for the quantitative prediction of bacteria-material interactions are based on colloidal theories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 93 publications
0
20
0
2
Order By: Relevance
“…A biomaterial's surface topography is generally considered to be an important parameter in biofilm formation. Features such as crevices, asperities, voids, or porosity on the order of the size of the bacteria are believed to provide shelter against biological fluid flow (that is, shear) and phagocytes . In contrast to the size of eukaryotic cells which have typical diameters of between 10 µm and 100 µm, bacteria are miniscule, with cell dimensions of about 0.2 µm in diameter × 2–8 µm length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A biomaterial's surface topography is generally considered to be an important parameter in biofilm formation. Features such as crevices, asperities, voids, or porosity on the order of the size of the bacteria are believed to provide shelter against biological fluid flow (that is, shear) and phagocytes . In contrast to the size of eukaryotic cells which have typical diameters of between 10 µm and 100 µm, bacteria are miniscule, with cell dimensions of about 0.2 µm in diameter × 2–8 µm length.…”
Section: Discussionmentioning
confidence: 99%
“…In their planktonic state, their motility is affected by various physical and electrokinetic forces, including Brownian motion, van der Waals attraction, Columbic attraction or repulsion, and even gravity . Several analytical models have been developed to explain their movement and attachment mechanisms, the most advanced of which is the Extended DLVO theory . Within the biological medium, it accounts for electrokinetic interactions of individually dispersed bacterium and the prosthetic surface including surface roughness, hydrophilic, and hydrophobic effects.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo experimentation is complemented by mathematical modeling. There are three accepted theories that describe attachment of charged molecules or cells to a substratum in a liquid environment: Derjaguin–Landau–Verwey–Overbeek (DLVO), Lifshitz–van der Waals (LW) acid–base (AB) approach to thermodynamic theory and extended DLVO (XDLVO) theory 80.…”
Section: Bacterial Biofilm Formationmentioning
confidence: 99%
“…Adhesion was higher on the CH 3 followed by the positively charged NH 2 , the non-charged NH 2 groups, the COOH, and minimal on the OH-terminated glass, in accordance with the predictions of the thermodynamic theory. 100,101 However, both studies showed that the increase in the shear rate restricted the predictability of the theory, suggesting the importance of nature of environment on bacterial adhesion. 99,100 Surface roughness is a two-dimensional parameter of a material surface and is generally characterized as the value of arithmetical mean deviation of the height profile (R a ).…”
Section: Biomaterials Surface Properties Affect Bacterial Adhesionmentioning
confidence: 96%
“…165 The fluid dynamics in flow chambers have been characterized elsewhere. 160 Another configuration of chambers is that of the radial flow chamber. It consists of two flat disks separated by a thin gap, and the fluid flows in through the center of the fixed disc and flows out radially through the gap between the discs.…”
Section: Dynamic Fluid Bacterial Adhesion Assaymentioning
confidence: 99%